Організація та управління програмами адаптивної фізичної культури у реабілітаційних центра для військових - Бочкарев, Сергій Володимирович; Євтифієв, Андрій Сергійович; Євтифієва, Ірина Ігорівна (Український державний університет імені Михайла Драгоманова, 2025)
У статті розглядаються сучасні підходи до організації та управління програмами адаптивної фізичної культури у реабілітаційних центрах для військовослужбовців. На основі аналізу вітчизняного та міжнародного досвіду (зокрема, країн НАТО) визначено ключові чинники ефективної реабілітації, серед яких: індивідуалізований підхід до розробки програм з урахуванням виду та ступеня уражень, застосування інноваційних технологій, а також комплексний психологічний супровід. Запропоновано практичні рекомендації щодо вдосконалення державного регулювання у цій сфері, включаючи: розробку стандартизованих програм на основі доказової медицини; створення ефективної системи міжвідомчої взаємодії; впровадження сучасних методів оцінки ефективності реабілітації. Особливу увагу приділено критеріям оцінки якості реабілітаційних послуг, таким як: динаміка фізичного відновлення, рівень соціальної адаптації та суб'єктивна оцінка пацієнтами результатів лікування. Результати дослідження підтверджують доцільність застосування комплексного підходу, що поєднує організаційні, медичні та соціальні аспекти реабілітаційного процесу.

This study investigates the organizational and managerial aspects of adaptive physical culture programs in military rehabilitation centers, with particular focus on optimizing rehabilitation outcomes for veterans with combat-related injuries. The research employs a comprehensive methodology combining systematic literature review, comparative analysis of international best practices (particularly from NATO countries), and evaluation of existing Ukrainian rehabilitation models. Key findings highlight three critical success factors: personalized rehabilitation programs tailored to specific injury profiles, integration of cutting-edge technologies including tele-rehabilitation platforms and immersive virtual reality systems, and implementation of trauma-informed psychological support throughout the rehabilitation process. The study demonstrates how tele-rehabilitation solutions overcome geographical barriers to care continuity, while VR technologies significantly enhance both physical recovery and cognitive rehabilitation through gamified therapeutic interventions. The paper proposes a framework for enhancing regulatory mechanisms, emphasizing: standardized evidence-based protocols, inter-institutional collaboration networks, and quality assurance systems incorporating digital monitoring tools. Quantitative and qualitative evaluation metrics are established, assessing physical recovery parameters, psychosocial reintegration indicators, and patient-reported satisfaction levels. Comparative analysis reveals that successful international models combine centralized quality control with local implementation flexibility – an approach particularly relevant for Ukraine's post-war rehabilitation infrastructure development. The research identifies current gaps in Ukraine's APC system, including uneven resource distribution and insufficient specialist training, while proposing targeted solutions based on adaptable NATO frameworks. Practical implications include: optimized resource allocation algorithms, competency standards for rehabilitation teams, and technology integration guidelines. The study concludes that effective military rehabilitation requires synergistic coordination between medical, physical, and psychosocial interventions, supported by robust management systems and innovative technological solutions. Future research directions should examine long-term outcomes of technology-assisted rehabilitation and economic models for sustainable program implementation.
Organization and management of adaptive physical culture programs in rehabilitation centers for military
Keywords: адаптивна фізична культура; реабілітація військових; управління програмами; телереабілітація; соціальна реінтеграція; adaptive physical culture; military rehabilitation; program management; tele-rehabilitation; social reintegration